PENERAPAN SISTEM AKUNTANSI RENCANA ANGGARAN BIAYA PROYEK PADA PT. DUTA INSTRUMENT ALFA SAKTI - Desy Arigawati; Galang Fardian (Pusat Riset dan Inovasi Nasional, 2022)
This writing aims to understand the implementation of the budget plan system carried out on a company's project. This study will prove the functioning of the accounting system in the project cost budget plan within a company, how to minimize expenses and the income obtained can be used efficiently. So that the accounting information for the project budget plan can be a reference for company management in making decisions. This information is used by the company and has an important role in achieving the success of a company in the future.